The Relationship between Dst, IMF-Bz and Collision Parameters for O+ + N2 ? NO+ + N Reactive Scattering in the Ionosphere - Sagir, Selcuk; Yasar, Mehmet; Atici, Ramazan (Pleiades Publishing Ltd, 2019)
The kinetic theory is particularly suitable and convenient to calculate the collision parameters in the ionospheric medium. In this study, the mean free path (lambda) and total collision numbers (Z(12)) for the O+ + N-2 -> NO+ + N reaction occurring in the ionospheric F region were calculated separately on geomagnetically quiet and disturbed days over Istanbul, Turkey. The relationship between geomagnetic Dst, solar IMF-Bz indices and the obtained results (lambda and Z(12)) by kinetic theory were investigated by the statistical multiple regression model. As a result of the investigation, it was seen that Dst and IMF-Bz are related to the mean free path and the total collision number on all days. It was found that IMF-Bz has a positive effect on the mean free path and the total collision number, and has a greater effect on lambda and Z(12) than Dst in all conditions. For both parameters, it was observed that the effect of Dst and IMF-Bz on quiet days was more than on disturbed days. Therefore, it can be argued that the mean free path decreases on disturbed days, especially during nighttime.
Keywords: Ionospheric F-Region; Temperature-Dependence; Oxygen; Ions